Non-functional oncocytic adrenocortical carcinoma: Case report with clinicopathologic and surgical correlation - Induparkavi Murugesan; Vikas Kailashiya; Sahil Data; Madan Gopal Bhardwaj; Sameer Trivedi (Urology Case Reports)
Oncocytic adrenocortical carcinoma (OACC) is a rare variant of adrenocortical carcinoma composed predominantly of oncocytic cells. We present the case of a 45-year-old female with a large, non-functional left adrenal mass diagnosed as OACC. Imaging revealed a well-defined, vascular, heterogeneously enhancing mass without metastasis. Histopathology showed oncocytic cells disposed in nests and sheets with capsular and venous invasion, with low mitotic activity. Surgical excision was curative, and the patient remains disease-free at 10 months. This case highlights the diagnostic and prognostic utility of histologic scoring systems and underlines the role of surgery as the primary treatment in localized OACC.